2016
DOI: 10.1016/j.annemergmed.2016.08.283
|View full text |Cite
|
Sign up to set email alerts
|

268 The Comparative Effectiveness of Three Junctional Tourniquet Devices in Human Volunteers

Abstract: of door-to-imaging. We chose door-to-imaging time because it is an objective measure of adherence to the American Heart Association Get With The Guidelines program and is primarily under the control of ED work environment and personnel.Methods: This was a retrospective analysis of prospectively collected registry data for all patients who presented to the ED of our urban, academic, regional stroke center between June 15, 2014 and June 14, 2015 for whom the stroke team was activated. Trained abstractors reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our observation is supported by Gaspary et al’s conference abstract, which reported 43% success rates of SJT ® on litter-carried patients. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation is supported by Gaspary et al’s conference abstract, which reported 43% success rates of SJT ® on litter-carried patients. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our observation is supported by Gaspary et al's conference abstract, which reported 43% success rates of SJT ® on litter-carried patients. [24] Undeniably, survival rates for bleeding trauma patients are inversely proportional to the time it takes to stop bleeding. Hence, in our study, demonstrating decreased ATs and increased success rates were anticipated outcomes in the aftertraining period.…”
Section: Discussionmentioning
confidence: 99%